Design of a precise electronic system for conductivity or resistivity measurement - Jin, Chi (2009)
This report gives a full description of the MSc (Power Engineering) Application for ISM Project 07/08-I-D 48 on “Design of a Precise Electronic System for Conductivity or Resistivity Measurement.” This project presented the design of an electronic system for resistivity measurement, including an current source circuit and a differential voltmeter. This electronic system for resistivity measurement would be validated using the Two-Electrode method which was proposed by this project supervisor and his Ph.D. Research student. This report will also describe the equipments, experiment set-up and procedures.